KADAR N, P, K, Ca JARINGAN SAWI PADA LAHAN YANG DIBERI AIR BM SAPI DAN BOKASHI DENGAN PENAMBAHAN BEBERAPA BAHAN PENINGKAT HARA - Lena Walunguru; Aloysius Ng. Lende; Mochammad Hasan (Politeknik Pertanian Negeri Kupang, 2009)
Degree of N, P, K, Ca Mustard Green Network In Tune That Given Water Bm Cow And Bokashi With Add Several Ingredients To Increase Hara. Organic farming use organic fertilizer such as compost, bokashi, and cattle BM fertilizer. Input of organic fertilizer can decrease by increae the quality of bokashi by apply ash, eggshell powder, and cow crine. Ash to increase potassium, eggshell powder is source of calcium, and cow crine source of nitrogen. The research used Completely Randomized Block Design consisting of seven treatments were bokashi without cattle BM fertilizer and bokashi (SBo), cattle BM fertilizer and bokashi added ash (SB1), cattle BM fertilizer and bokashi added cowurine (SB2), cattle BM fertilizer and bokashi added eggshell powder (SB3), cattle BM fertilizer and bokashi added ash and cow urine (SB4), cattle BM fertilizer and bokashi added ash and eggshell powder (SB5), cattle BM fertilizer and bokashiadded ash and, eggshell powder and cow urine (SB6). The data was anayzed byusing Analysis of Variance and Honestly Significant Difference (HSD) at 5%. The result showed that cattle BM fertilizer and bokashi added ash, cattle BM fertilizer and bokashi added cow urine, and cattle BM fertilizer and bokashi added eggshell powder, each increasing potassium, nitrogen and calcium nutrient of soil,so that impact to potassium, nitrogen dan calcium of plant tissue. Cattle BM fertilizer and bokashi added cow urine significant to increasing dry plant weigh amount 28,57%. Key word: cattle BM fertilizer, bokashi, nutrient